2020
DOI: 10.22271/chemi.2020.v8.i2u.8956
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dates of sowing with residual nutrient of preceding crop and direct impact of nutrients at varying levels on yield, nutrient uptake and economics of buckwheat (Fagopyrum esculentum) in northern hills of Chhattisgarh

Abstract: A field experiment was conducted in two consecutive rabi 2016-17 and 2017-18, at Mainpat, Chhattisgarh to find out the suitable date of sowing, residual nutrient of preceding crop and direct effect of nutrient at varying levels on succeeding buckwheat for obtaining higher productivity, profitability nutrient uptake and quality of local buckwheat cultivars in hilly area of Chhattisgarh. The experiment was laid out in split-split plot design with three date of sowing viz., D1-1 st week of October, D2-3 rd week o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…This could be because of increased amount of leftover nutrients linked with the increased fertility levels used in the previous rice harvest, which affected crop growth and yield attributes, ultimately enhancing the grain yield of the succeeding maize. The findings were consistent with those of Rathiya et al (2020) and Pradhan et al (2021), who found that leftover nutrients had a favourable effect on the yield of the next crop that recorded the highest grain yield.…”
Section: Grain Yield (Kg Ha -1 )supporting
confidence: 92%
“…This could be because of increased amount of leftover nutrients linked with the increased fertility levels used in the previous rice harvest, which affected crop growth and yield attributes, ultimately enhancing the grain yield of the succeeding maize. The findings were consistent with those of Rathiya et al (2020) and Pradhan et al (2021), who found that leftover nutrients had a favourable effect on the yield of the next crop that recorded the highest grain yield.…”
Section: Grain Yield (Kg Ha -1 )supporting
confidence: 92%